Geological Mapping and Spring Water Quality Analysis in Mehara Village, Tutuala Administrative Post, Lautém Municipality - Santos, Juvencio Dos; Gome, Ricardo; Santos, Igildo Dos; L.Guterres, Abrão Luis A. da; Ribeiro, Gregorio da Costa; Guterres, Juvinal X. (Jurnal Locus Penelitian dan Pengabdian, 2025)
The study area for the final project is located along the east coast of Timor Island, within the Lautém municipality, specifically in the post-administrative region of Tutuala, Village of Mehara, with coordinates 127° 9’ 0’’ E - 127° 12’ 0’’ E and 08° 22’ 30’’ S - 08° 25’ 30’’ S, covering a total area of 6 x 6 km (36 km²). The research area consists of two lithological units: massif coral siltstone and coral sandstone. The lithology types present in the study area indicate three different geomorphologic units: lagoon, karst morphogenesis unit, and fluvial morphogenesis unit. There are three springs: Ira Veru spring, Ira Masi spring, and Lagoon Ira Lalaru, which are permanent water sources used to analyze physical, chemical, and bacteriological parameters. According to laboratory tests on water quality from the collected springs, the physical and chemical properties are within normal ranges; however, the bacteriological parameters show a high presence of coliform microbes, including E. coli. The presence of these microbes in the water affects the quality of groundwater and influences the degree of contamination in drinking water. The type of contamination present in the water is both punctual and diffuse, which impacts community life.